Nur Farah Nuha UMPSAs Student Entrepreneurship Icon - Halizan, Mohmood (UMPSA, 2024)
GAMBANG, 23 January 2024 - Coffee has been the main beverage in Malaysian society for ages. While it used to be served plain without sugar and black, coffee has evolved, now offering various aromas and additional flavours such as latte, americano, brew, and others, attracting diverse groups of buyers.